The Effect of Internet Financial Reporting, Website Information Disclosure Level, Shares Outstanding, Stock Prices, On Stock Trading Frequency - Dewi, Kadek Ayu Silvi Septya; Atim Djazuli (Jurnal Management Risiko dan Keuangan, 2025)
The objective of this research is to identify the effects of internet financial reporting, website information disclosure level, shares outstanding, and stock prices on the stock trading frequency of LQ45 companies. This explanatory research attempts to identify the relationship between its variables through hypothesis testing. Using purposive technique, 24 companies were selected as the samples. In order to test the proposed hypotheses, multiple linear regression analysis was employed. This research finds that internet financial reporting, website information disclosure level, and stock prices do not have any significant effect on the stock trading frequency of the LQ45 companies, that shares outstanding have a positive and significant effect on the stock trading frequency of the companies, and that internet financial reporting, website information disclosure level, shares outstanding, and stock prices simultaneously have significant impact on the stock trading frequency of the said companies.